Taphonomy of a village: the early 20th century site of Mariano Miró (Chapaleufú department, La Pampa, Argentina) - Landa, Carlos Gilberto (2014)
The Mariano Miró archaeological site (Chapaleufú Department, La Pampa Province, Argentina) was a town of nearly 500 inhabitants, founded in 1901 and abandoned in 1911. From the Historical Archaeology perspective, this paper aims to reconstruct the taphonomic histories of surface artifact assemblages from the Mariano Miró ghost town. We analyze taphonomic processes at both the artifact and the assemblage level, considering multiple variables including size, thermal alteration, weathering, site topography, trampling, anthropic activities and burrowing animal activities. We use GIS to interrelate the selected variables and assess the roles of various taphonomic agents in shaping the characteristics and distributions of materials at Mariano Miró. The information pertaining to formation processes obtained from Mariano Miró is potentially useful for generating expectations for and understanding other sites in the region that exhibit similar taphonomic conditions.